Age-Related Changes in the Thermoregulatory Properties in Bank Voles From a Selection Experiment - Grosiak, Marta; Koteja, Paweł; Bauchinger, Ulf; Sadowska, Edyta T. (Frontiers in Physiology, 2020)
As many physiological performance traits, the capacity of endotherms to thermoregulate declines with age. Aging compromises both the capacity to conserve or dissipate heat and the thermogenesis, which is fueled by aerobic metabolism. The rate of metabolism, however, not only determines thermogenic capacity, but can also affect the process of aging. Therefore, we hypothesized that selection for an increased aerobic exercise metabolism, which has presumably been a crucial factor in evolution of endothermic physiology in the mammalian and avian lineages, affects not only the thermoregulatory traits, but also the age-related changes of these traits. Here we test this hypothesis on bank voles (Myodes glareolus) from an experimental evolution model system: four lines selected for high swim-induced aerobic metabolism (A lines), which have also increased the basal, average daily, and maximum cold-induced metabolic rates, and four unselected control (C) lines. We measured the resting metabolic rate (RMR), evaporative water loss (EWL) and body temperature in 72 young adult (4 month) and 65 old voles (22 months) at seven ambient temperatures (13 to 32 °C). The RMR was 6% higher in A than C lines, but, regardless of the selection group or temperature, it did not change with age. However, EWL was 12% higher in the old voles. A decreased RMR/EWL ratio implies either a compromised efficiency of oxygen extraction in lungs or increased skin permeability. This effect was more profound in the A lines, which may indicate their increased vulnerability to ageing. Body temperature did not differ between the selection or age groups below 32 °C, but at 32 °C it was markedly higher in the old A-line voles than in those from other groups. As expected, the thermogenic capacity, measured as the maximum cold-induced oxygen consumption, was decreased by about 13% in the old voles from both selection groups, but the performance of old A-line voles was the same as that of young C-line ones. Thus, the selection for high aerobic exercise metabolism attenuated the adverse effects of aging on cold tolerance, but this advantage has been traded off by a compromised coping with hot conditions by aged voles.